2019
DOI: 10.29333/iejme/5940
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Effect Implementing the Jigsaw Strategy on the Academic Achievement of Students in Mathematics Classes

Abstract: The prime purpose of the current study was to investigate the effect of the predictive power of Jigsaw strategy on low proficient students' proficiency in mathematics and determine the effect of Jigsaw strategy on the mathematics achievement of middle-grades grade-two students. The current study included 80 students who were enrolled in the mathematics lessons in 2017-2018 academic year. Of the total sample, forty were included in an experimental group and forty were in control group. The experimental group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The Jigsaw co-operative learning strategy is one type of co-operative learning strategy. According to Abed, Sameer, Kasim, and Othman (2019), Jigsaw co-operative learning strategy is defined as a small group learning strategy in which each member striving to be an 'expert' on any one given learning activity for their common goal success in the absence of competition. This Jigsaw method in the context of the current study was applied in the mathematics laboratory by forming Jigsaw group consisting of 4 or 5 learners which seems to be convenient in each laboratory class learning environment.…”
Section: Jigsaw Co-operative Methods Combined With Geogebra As Learninmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jigsaw co-operative learning strategy is one type of co-operative learning strategy. According to Abed, Sameer, Kasim, and Othman (2019), Jigsaw co-operative learning strategy is defined as a small group learning strategy in which each member striving to be an 'expert' on any one given learning activity for their common goal success in the absence of competition. This Jigsaw method in the context of the current study was applied in the mathematics laboratory by forming Jigsaw group consisting of 4 or 5 learners which seems to be convenient in each laboratory class learning environment.…”
Section: Jigsaw Co-operative Methods Combined With Geogebra As Learninmentioning
confidence: 99%
“…This implies the role of Jigsaw II method in learners' physics concept learning was paramount. Abed et al (2019) examined the effect of the predictive power of Jigsaw strategy on low proficient students' proficiency in mathematics and on their achievement of grade-two students enrolled in 2017-2018. The sample size was 80 in both the experimental and comparison groups.…”
Section: Jigsaw Co-operative Learning Strategymentioning
confidence: 99%
“…This type of research includes quantitative research. It highlights that all collected data would go through some calculations before answering the research question in the study (33). In the current study, we have the training together style utilized in executing the cooperative learning strategy style and the traditional training technique for identifying the activity of handball classes.…”
Section: Methodsmentioning
confidence: 99%
“…A study has shown that achievement levels are higher for the students taught using Jigsaw collaborative method than the students taught with conventional teaching methods (Suresh and Reddy, 2017). The findings of few research studies have showed that Jigsaw strategy had more positive effect on students' overall mathematics achievement than the control group students (Abed et al, 2019;Yemi et al, 2018). Furthermore, Jigsaw is perceived as teacher-friendly collaborative learning method that can be readily applicable for the task of problem-solving (Ghaith, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%